2015
DOI: 10.1371/journal.pone.0129997
|View full text |Cite
|
Sign up to set email alerts
|

zflncRNApedia: A Comprehensive Online Resource for Zebrafish Long Non-Coding RNAs

Abstract: Recent transcriptome annotation using deep sequencing approaches have annotated a large number of long non-coding RNAs in zebrafish, a popular model organism for human diseases. These studies characterized lncRNAs in critical developmental stages as well as adult tissues. Each of the studies has uncovered a distinct set of lncRNAs, with minor overlaps. The availability of the raw RNA-Seq datasets in public domain encompassing critical developmental time-points and adult tissues provides us with a unique opport… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 38 publications
(40 reference statements)
0
18
0
1
Order By: Relevance
“…Using the in-house “RNA-seq data analysis pipeline”, we obtained our final dataset with more zebrafish lncRNAs, containing in total 13,604 lncRNA genes (21,128 transcripts) (Additional file 2 ). The major data sources of our lncRNA set are from RNA-seq data analysis and NONCODE [ 22 ], followed by NCBI, Ensembl and zflncRNApedia orderly [ 23 25 ] (Fig. 1b ).…”
Section: Resultsmentioning
confidence: 99%
“…Using the in-house “RNA-seq data analysis pipeline”, we obtained our final dataset with more zebrafish lncRNAs, containing in total 13,604 lncRNA genes (21,128 transcripts) (Additional file 2 ). The major data sources of our lncRNA set are from RNA-seq data analysis and NONCODE [ 22 ], followed by NCBI, Ensembl and zflncRNApedia orderly [ 23 25 ] (Fig. 1b ).…”
Section: Resultsmentioning
confidence: 99%
“…Transcriptomic studies of early embryonic development 23,25 and five adult tissues 26 have identified over 2,000 lncRNAs in zebrafish 27 , of which 727 have been confirmed as noncoding based on ribosome occupancy patterns 28 . For our knockout study we selected 24 bona fide lncRNAs based on conservation, expression dynamics and proximity to developmental regulatory genes (see Fig 1 for selection criteria for each lncRNA).…”
mentioning
confidence: 99%
“…Regulation of kalrna by lncRNA is not known. Thus, we checked for presence of any lncRNA near the 5′ locus of kalrna in the zebrafish lncRNA database zflncRNApedia (Dhiman et al, 2015). We found one such lncRNA ZF_LNC002146 in the database; although its location is ~72 kb away from kalrna according to Zv9 annotation, overlaps with extended 5′ exon of kalrna in Zv10 (Figure 1A).…”
Section: Resultsmentioning
confidence: 99%